Atlas® Listeria monocytogenes LmG2 Detection Assay Using Transcription Mediated Amplification to Detect Listeria monocytogenes in Selected Foods and Stainless Steel Surface. (27th November 2019) - Bres, Vanessa; Yang, Hua; Hsu, Ernie; Ren, Yan; Cheng, Ying; Wisniewski, Michele; Hanhan, Maesa; Zaslavsky, Polina; Noll, Nathan; Weaver, Brett; Campbell, Paul; Reshatoff, Michael; et al.
Abstract: The Atlas Listeria monocytogenes LmG2 Detection Assay, developed by Roka Bioscience Inc., was compared to a reference culture method for seven food types (hot dogs, cured ham, deli turkey, chicken salad, vanilla ice cream, frozen chocolate cream pie, and frozen cheese pizza) and one surface (stainless steel, grade 316). A 125 g portion of deli turkey was tested using a 1:4 food:media dilution ratio, and a 25 g portion for all other foods was tested using 1:9 food:media dilution ratio. The enrichment time and media for Roka's method was 24 to 28 h for 25 g food samples and environmental surfaces, and 44 to 48 h for 125 g at 35 ± 2°C in PALCAM broth containing 0.02 g/L nalidixic acid. Comparison of the Atlas Listeria monocytogenes LmG2 Detection Assay to the reference method required an unpaired approach. For each matrix, 20 samples inoculated at a fractional level and five samples inoculated at a high level with a different strain of Listeria monocytogenes were tested by each method. The Atlas Listeria monocytogenes LmG2 Detection Assay was compared to the Official Methods of Analysis of AOAC INTERNATIONAL 993.12 method for dairy products, the U.S. Department of Agriculture, Food Safety and Inspection Service, Microbiology Laboratory Guidebook 8.08 method for ready-to-eat meat and environmental samples, and the U.S. Food and Drug Administration Bacteriological Analytical Manual, Chapter 10 method for frozen foods. In the method developer studies, Roka's method, at 24 h (or 44 h for 125 g food samples), had 126 positives out of 200 total inoculated samples, compared to 102 positives for the reference methods at 48 h. In the independent laboratory studies, vanilla ice cream, deli turkey and stainless steel grade 316 were evaluated. Roka's method, at 24 h (or 44 h for 125 g food samples), had 64 positives out of 75 total inoculated samples compared to 54 positives for the reference methods at 48 h. The Atlas Listeria monocytogenes LmG2 Detection Assay detected all 50 L. monocytogenes strains that encompassed 13 serotypes across the various lineages and none of the 30 exclusive organisms, including seven other Listeria species. The product consistency and kit stability studies revealed no statistical differences between the three lots tested or to the term of the shelf life. Finally, the robustness study demonstrated no statistical differences when samples were incubated at 33 ± 2°C or 37 ± 2°C, when enrichment aliquots were 1.3 mL or 1.7 mL, or when the samples were analyzed the same day or five days later. Overall the Atlas Listeria monocytogenes LmG2 Detection Assay is statistically equivalent to or better than the reference methods and is robust to the tested variations.